2019
DOI: 10.1002/1878-0261.12566
|View full text |Cite
|
Sign up to set email alerts
|

TRPM4 is highly expressed in human colorectal tumor buds and contributes to proliferation, cell cycle, and invasion of colorectal cancer cells

Abstract: Abbreviations CD, current density; CRC, colorectal cancer; TBC, tumor border configuration; TRPM4, transient receptor potential melastatin-4 channel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(65 citation statements)
references
References 39 publications
2
63
0
Order By: Relevance
“…TRPM4 expression levels have been investigated in a number of different cancers ( Figure 2 ) [ 32 , 33 , 34 , 38 , 39 , 40 , 41 , 101 , 102 , 103 , 104 , 105 , 106 ]. In most studies, TRPM4 protein expression levels were reported to be increased in tumor samples compared to healthy tissue.…”
Section: Trpm4 Expression In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…TRPM4 expression levels have been investigated in a number of different cancers ( Figure 2 ) [ 32 , 33 , 34 , 38 , 39 , 40 , 41 , 101 , 102 , 103 , 104 , 105 , 106 ]. In most studies, TRPM4 protein expression levels were reported to be increased in tumor samples compared to healthy tissue.…”
Section: Trpm4 Expression In Cancermentioning
confidence: 99%
“…However, another study using TRPM4 knockout mice reported no differences in glucose-induced insulin release compared to wild-type mice [ 14 ]. Lately, growing interest has been directed toward TRPM4 and its role in several types of cancer [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. TRPM4 contributes to several cancer hallmark functions, such as cell migration, proliferation, and the epithelial to mesenchymal transition (EMT).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TRPM4-mediated Na + influx was shown to regulate cell viability and the cell cycle of HCT116 cells. In the same study, TRPM4 was also linked to the regulation of CRC cells migration and invasion [122].…”
Section: Colorectal Cancermentioning
confidence: 88%
“…For example, TRPM7 is upregulated in pre-malignant pancreatic cancer compared to normal pancreatic tissue [103], and so it could potentially serve as a candidate for a pancreatic cancer biomarker. Another candidate for a novel biomarker could be TRPM4, which was shown to be highly expressed in tumor buds in CRC cancer tissues [122]. Currently, there is a need for the introduction of novel additional biomarkers, which could support the TNM staging system [155].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, other KCTD proteins regulate ion channels function [ 40 , 61 , 62 ]. Interestingly, KCTD5 is involved in the regulation of TRPM4 activity, a well-described ion channel related to cell migration [ 40 , 41 , 63 , 64 , 65 ]. Therefore, it could be plausible that the KCTD5-dependent effects in Ca 2+ response are the result of the action of KCTD5 on the ion channels function.…”
Section: Discussionmentioning
confidence: 99%